A Concise Copper-Catalyzed Oxytrifluoromethylation of Allyl Alcohols - Chen, Longhui; Yang, Zequn; Sun, Qi; Guo, Minjie; Feng, Xintong; Tang, Xiangyang; Wang, Guangwei (Synthesis, 2021)
An efficient oxytrifluoromethylation of 1-aryl-substituted allyl alcohols has been developed using Togni’s reagent II as a trifluoromethylation reagent and copper(I) chloride as a catalyst. This reaction proceeded through a one-pot process of trifluoromethylation followed by nucleophilic attack of the vicinal hydroxyl group. This strategy features good diastereoselectivity and broad substrate scope, which provides a facile access to various 2-aryl-3-(2,2,2-trifluoroethyl)oxiranes.
Keywords: oxytrifluoromethylation; allyl alcohols; CF3-substituted epoxides; Togni’s reagent; copper catalysis; 2-(2,2,2-trifluoroethyl)oxiranes